2018
DOI: 10.1038/s41598-018-29053-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and pattern of exercise and depression after two years in older Japanese adults: the JAGES longitudinal study

Abstract: Few have clarified what exercise frequencies and patterns (e.g. alone or with others) are effective for preventing depression in older adults. We examined the relationship between total frequency and/or pattern of exercise and the risk of depression after two years in older Japanese adults. We used a sub-sample of the Japan Gerontological Evaluation Study (JAGES) performed in 2011 and 2013. The sample for analysis was 1,422 adults aged 65 years or older without depression and low physical strength in 2011. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 40 publications
(51 reference statements)
3
42
0
1
Order By: Relevance
“…Engaging in group sports and exercise has been reported to reduce the risk of functional disability, (Kanamori et al, 2012) depressive symptoms, (Kanamori et al, 2018) and falls (Hayashi et al, 2018) among older people, compared to engaging in sports and exercise alone. The suspected mechanisms between sports and exercise group participation and health outcomes generally involve the benefits of physical activity (e.g., inducing good adherence and long duration), psychological factors (e.g., leading to enjoyment, enhanced self-esteem, and decreased stress), and social factors (e.g., receiving social support, social capital, and social influence) (Kanamori, Takamiya, & Inoue, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Engaging in group sports and exercise has been reported to reduce the risk of functional disability, (Kanamori et al, 2012) depressive symptoms, (Kanamori et al, 2018) and falls (Hayashi et al, 2018) among older people, compared to engaging in sports and exercise alone. The suspected mechanisms between sports and exercise group participation and health outcomes generally involve the benefits of physical activity (e.g., inducing good adherence and long duration), psychological factors (e.g., leading to enjoyment, enhanced self-esteem, and decreased stress), and social factors (e.g., receiving social support, social capital, and social influence) (Kanamori, Takamiya, & Inoue, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Much like other patients with chronic diseases, glaucoma patients are more likely to have depression with a reported prevalence of 10.9% in comparison with those without glaucoma (6.9%) [41]. Literature has shown that exercise reduces the incidence of depression or anxiety [8,42,43]. For example, Babyak M [44] investigated 156 adult volunteers with major depressive disorder for 10 months, and found that increasing exercise time lowers depression relapse rates in comparison to that of the medication group.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) is an essential part of daily life, with PA guidelines in the US advising adults to set aside time for at least 150 min to 300 min of moderate intensity PA per week or 75 min to 150 min of vigorous intensity aerobic PA per week to stay healthy [7]. The health benefits of PA have been widely documented for both systemic and ocular diseases including boosting the immune system, improving sleep quality, reducing the incidence of cardiac-cerebral vascular events and is correlated with decreased anxiety and depression rates [8][9][10][11][12]. For eyes in particular, exercise can decrease the IOP [13] and decreasing IOP is associated with the magnitude of exercise [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are several Nordic Walking Circles in which middle‐aged and older people can participate, and the development of the system and of the community might have contributed to the lower prevalence of depression observed in the present study. Another study mentions exercise frequency as a depression prevention measure for older adults, and exercising at least twice a week and/or with others might be useful in preventing depression …”
Section: Discussionmentioning
confidence: 99%
“…Another study mentions exercise frequency as a depression prevention measure for older adults, and exercising at least twice a week and/or with others might be useful in preventing depression. 30 The present study included participants with various background diseases, and it is assumed that there were participants with a high risk of developing depression in both the intervention and control groups. Previous studies have reported that two or more exercise sessions a week are effective in preventing depression.…”
Section: Discussionmentioning
confidence: 99%